Effect of light and temperature on seed germination in Tibouchina mutabilis (Vell.) Cogn. (Melastomataceae) - Simão, Edson [UNESP]; Takaki, Massanori [UNESP] (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2008)
A influência da luz e da temperatura na germinação de sementes de Tibouchina mutabilis foi avaliada sob incubações isotérmicas de 10 a 40 °C sob luz branca contínua (32,85 µmolm-2s-1), com intervalos de 5 °C e temperaturas alternadas (15-20; 15-25; 15-30; 15-35; 20-25; 20-30; 20-35; 25-30; 25-35 e 30-35 °C) sob fotoperíodo de 12 horas de luz branca. As sementes de T. mutabilis requerem luz para germinar, sendo nula a germinação no escuro em todas as temperaturas testadas. A faixa ótima de temperatura para a germinação foi de 25 a 30 °C e a alternância de temperaturas de 20-25 °C. Estes resultados indicam que T. mutabilis apresenta comportamento de uma espécie pioneira e que as alternâncias diárias de temperatura não alteraram a sensibilidade da semente à luz.

The effect of light and temperature on Tibouchina mutabilis seed germination was analyzed by isothermic incubations in the range of 10 to 40 °C, with 5 °C intervals under both continuous white light (32.85 µmolm-2s-1) and darkness and alternating temperatures (15-20; 15-25; 15-30; 15-35; 20-25; 20-30; 20-35; 25-30; 25-35 and 30-35 °C) under both photoperiod of 12 hours and continuous darkness. The seeds of T. mutabilis need light to trigger the germination and no germination was observed in darkness. The range of optimum temperatures for germination was between 25 to 30 °C and the 20-25 °C alternating temperatures. These results indicate that T. mutabilis behaves as a pioneer species and daily alternating temperatures did not change the light sensitivity of seeds.
Efeito da luz e da temperatura na germinação de sementes de Tibouchina mutabilis (Vell.) Cogn. (Melastomataceae)
Keywords: fitocromo; germinação de sementes; luz; Tibouchina; light; phytochrome; seed germination; Tibouchina